Chemotherapy in patients with localized angiosarcoma of any site: A retrospective european study. (August 2022) - Conforti, Fabio; Gronchi, Alessandro; Penel, Nicholas; Jones, Robin L.; Broto, Javier M.; Sala, Isabella; Bagnardi, Vincenzo; Napolitano, Andrea; Pala, Laura; Pennacchioli, Elisabetta; Catania, Chiara; Queirolo, Paola; et al.
Abstract: Background: We retrospectively investigated the role of (neo)adjuvant chemotherapy in patients with primary, localized angiosarcoma. Methods: We selected all patients with primary, localized angiosarcoma, who had received radical surgery between January 2005 and December 2019 at 33 European sarcoma reference centers. The primary objective was to compare the outcome of patients who received (neo)adjuvant chemotherapy versus those who did not, in terms of overall survival (OS), disease-free survival (DFS) and distant metastasis-free survival (DMFS). To reduce the risk of confounding due to imbalance, a propensity-score matching(PSM) was performed. Finally, subgroups analysis was performed according to tumor site, tumor size (< 50 mm or ≥ 50 mm) and patients predicted 10-years OS according to the nomogram sarculator (two different cutoff-values were applied: ≤ 33% or > 33% and < 60% or ≥ 60%). Results: 362 patients were analyzed: 149 (41.2%; treated group) received (neo) adjuvant chemotherapy and 213 (58.6%; control group) did not. The median follow-up for the OS endpoint was 5.1 years (95% CI: 4.0–5.5). The OS-HR was 0.58 (95%CI: 0.40–0.83; p-value = 0.003) in the univariate analysis and 0.74 (95% CI: 0.38–1.43; p = 0.367) in the PSM analysis. The DFS-HR was 0.75 (95% CI: 0.57–0.98; p-value = 0.036) in the univariate analysis, and 0.91 (95% CI:0.56–1.48; p-value = 0.7) in the PSM analysis. The DMFS-HR was 0.75 (95% CI: 0.55–1.02; p-value = 0.065) in univariate analysis and 0.92 (95% CI: 0.53–1.61; p-value = 0.769) in the PSM analysis. Subgroup analysis revealed no heterogeneity of results in strata of tumor site. On the contrary, there was a trend for heterogeneity according to tumor size and patient's risk of death. For all the endpoints analyzed, patients with tumors smaller than 50 mm or at lower risk of death seem to have no benefit from chemotherapy, while patients with larger tumors or at higher risk of death at 10 years seem to derive substantial benefit. Conclusion: This large, retrospective study suggests that patients affected by > 50 mm and/or high-risk primary, localized angiosarcoma could benefit from (neo)adjuvant chemotherapy. Highlights: Localized angiosarcoma of any site. Effectiveness of (neo)adjuvant chemotherapy. High risk angiosarcoma.